Flavonoid biosynthesis is differentially altered in detached and attached ripening bilberries in response to spectral light quality - Samkumar, Amos; Karppinen, Katja; McGhie, Tony K.; Espley, Richard V.; Martinussen, Inger; Jaakola, Laura (Frontiers in Plant Science, 2022)
Light spectral quality is known to affect flavonoid biosynthesis during fruit ripening. However, the response of fruits to different light conditions, when ripening autonomously from the parent plant (detached), has been less explored. In this study, we analyzed the effect of light quality on detached and naturally ripening (attached) non-climacteric wild bilberry (Vaccinium myrtillus L.) fruits accumulating high amounts of anthocyanins and flavonols. Our results indicated contrasting responses for the accumulation of phenolic compounds in the berries in response to red and blue light treatments. For detached berries, supplemental blue light resulted in the highest accumulation of anthocyanins, while naturally ripening berries had elevated accumulation under supplemental red light treatment. Both red and blue supplemental light increased the expression levels of all the major structural genes of the flavonoid pathway during ripening. Notably, the key regulatory gene of anthocyanin biosynthesis, VmMYBA1, was found to express five-fold higher under blue light treatment in the detached berries compared to the control. The red light treatment of naturally ripening berries selectively increased the delphinidin branch of anthocyanins, whereas in detached berries, blue light increased other anthocyanin classes along with delphinidins. In addition, red and far-red light had a positive influence on the accumulation of flavonols, especially quercetin and myricetin glycoside derivatives, in both ripening conditions. Our results of differential light effects on attached and detached berries, which lacks signaling from the mother plant, provide new insights in understanding the light-mediated regulatory mechanisms in non-climacteric fruit ripening.